Associations between preoperative anaemia and hospital costs following major abdominal surgery: cohort study. Issue 2 (7th April 2021) - Meyerov, J; Louis, M; Lee, D K; Fletcher, L; Banyasz, D; Miles, L F; Ma, R; Tosif, S; Koshy, A N; Story, D A; Bellomo, R; Weinberg, L
Abstract: Background: Determining the cost-effectiveness and sustainability of patient blood management programmes relies on quantifying the economic burden of preoperative anaemia. This retrospective cohort study aimed to evaluate the hospital costs attributable to preoperative anaemia in patients undergoing major abdominal surgery. Methods: Patients who underwent major abdominal surgery between 2010 and 2018 were included. The association between preoperative patient haemoglobin (Hb) concentration and hospital costs was evaluated by curve estimation based on the least-square method. The in-hospital cost of index admission was calculated using an activity-based costing methodology. Multivariable regression analysis and propensity score matching were used to estimate the effects of Hb concentration on variables related directly to hospital costs. Results: A total of 1286 patients were included. The median overall cost was US $18 476 (i.q.r.13 784–27 880), and 568 patients (44.2 per cent) had a Hb level below 13.0 g/dl. Patients with a preoperative Hb level below 9.0 g/dl had total hospital costs that were 50.6 (95 per cent c.i. 14.1 to 98.9) per cent higher than those for patients with a preoperative Hb level of 9.0–13.0 g/dl ( P  <   0.001), 72.5 (30.6 to 128.0) per cent higher than costs for patients with a Hb concentration of 13.1–15.0 g/dl ( P  <   0.001), and 62.4 (21.8 to 116.7) per cent higher than those for patients with a Hb level greater than 15.0 g/dl ( P  <   0.001). Multivariable general linear modelling showed that packed red blood cell (PRBC) transfusions were a principal cost driver in patients with a Hb concentration below 9.0 g/dl. Conclusion: Patients with the lowest Hb concentration incurred the highest hospital costs, which were strongly associated with increased PRBC transfusions. Costs and possible complications may be decreased by treating preoperative anaemia, particularly more severe anaemia. Abstract : In a cost analysis of preoperative anaemia in 1 286 patients undergoing major abdominal surgery, increasing preoperative anaemia severity was found to be associated with higher hospital costs and poorer patient outcomes. This study highlights preoperative anaemia as a useful target for cost and complication minimisation.